2022
DOI: 10.3390/brainsci13010051
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Long-Term Recovery of Consciousness in Prolonged Disorders of Consciousness Based on Coma Recovery Scale-Revised Subscores: Validation of a Machine Learning-Based Prognostic Index

Abstract: Prognosis of prolonged Disorders of Consciousness (pDoC) is influenced by patients’ clinical diagnosis and Coma Recovery Scale-Revised (CRS-R) total score. We compared the prognostic accuracy of a novel Consciousness Domain Index (CDI) with that of clinical diagnosis and CRS-R total score, for recovery of full consciousness at 6-, 12-, and 24-months post-injury. The CDI was obtained by a combination of the six CRS-R subscales via an unsupervised machine learning technique. We retrospectively analyzed data on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…The selected studies included an overall sample of 2844 patients with disorders of consciousness (eight in coma, 0.3%; 1774 in VS/UWS, 62.4%; 926 in MCS, 32.6%; 136 having emerged from MCS [eMCS], 4.7%) caused by different aetiologies (traumatic brain injury 992, 34.9%; non‐traumatic brain injury 1852, 65.1%), with a mean age of 48 years (not available in two studies); 1825 (64.2%) patients were male (not available in one study). Most studies [3, 5, 13–19, 21, 23, 24, 26, 31, 32, 35, 36, 39, 40] investigated the prognostic role of demographic, clinical and anamnestic factors. Some studies also included neurophysiological [5, 16, 19, 20, 22, 23, 25, 28, 30, 32, 33, 38] or neuroimaging [15, 26, 29, 37–39] investigations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected studies included an overall sample of 2844 patients with disorders of consciousness (eight in coma, 0.3%; 1774 in VS/UWS, 62.4%; 926 in MCS, 32.6%; 136 having emerged from MCS [eMCS], 4.7%) caused by different aetiologies (traumatic brain injury 992, 34.9%; non‐traumatic brain injury 1852, 65.1%), with a mean age of 48 years (not available in two studies); 1825 (64.2%) patients were male (not available in one study). Most studies [3, 5, 13–19, 21, 23, 24, 26, 31, 32, 35, 36, 39, 40] investigated the prognostic role of demographic, clinical and anamnestic factors. Some studies also included neurophysiological [5, 16, 19, 20, 22, 23, 25, 28, 30, 32, 33, 38] or neuroimaging [15, 26, 29, 37–39] investigations.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐three out of the 27 included studies reported all outcomes of interest. Three studies provided data from the same database, but Estraneo et al [5] reported data on patients' improvement at 6 months post‐injury, Estraneo et al [16] reported data on patients' mortality at 24 months post‐injury and Magliacano et al [17] only reported data on recovery of full consciousness at 24 months post‐injury. Moreover, Nekrasova et al [18] only reported data on patients' mortality (see PRISMA flow diagram in Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indices and measures derived from the CRS-R, including the CRS-R total score, the total scores in the subscales of the CRS-R, the clinical diagnosis, the CRS-R Modified Score, 16 the CRS-R Index, 17 the CRS+ 23 and the Consciousness Domain Index, 24 were estimated from the collected data as described in the corresponding manuscripts (Supplementary Digital Material 1: Supplementary Figure 1, 2, Supplementary Table I, II). It is worth to be noted that both CRS-R Modified Score and CRS-R Index calculated in this paper were approximations obtained from the scores on the subscales, instead of evaluating the neurobehavioral signs as required for their derivation.…”
Section: Methodsmentioning
confidence: 99%
“… 23 More recently, Magliacano and Liuzzi proposed the Consciousness Domain Index, an unsupervised machine learning clustering technique based on information from the CRS-R sub-scales to improve the prediction of recovery of consciousness. 24 …”
mentioning
confidence: 99%